2008
DOI: 10.1037/0893-164x.22.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting agreement between severely mentally ill alcohol abusers' and collaterals' reports of alcohol and other substance abuse.

Abstract: This study examined subject-collateral reports of alcohol use among a sample of 167 dually diagnosed individuals seeking outpatient treatment at a community mental health clinic. All subjects met Diagnostic and Statistical Manual of Mental Disorders (4th ed.; American Psychiatric Association, 1994) criteria for a schizophrenia-spectrum or bipolar disorder and for alcohol abuse or dependence. Subjects were recruited within 2 weeks of treatment entry and completed measures of cognitive functioning, alcohol depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
1
11
1
Order By: Relevance
“…Previous studies have reported sensitivity and specificity at 0.60 and 0.42 [10] and Spearman's correlation of approximately 0.4 [29], well below what we found in the present study. Other studies found kappas between 0.47 [11] and 0.9 [30], intraclass correlation (ICC) of 0.62 [31] and Yule's Y of 0.8 [32], being comparable or just below our correlation coefficients. In the cases where our study shows better agreement than previous studies, it is difficult to state whether this is due to the use of blood rather than urine, due to differences in sample populations or simply to statistical chance.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies have reported sensitivity and specificity at 0.60 and 0.42 [10] and Spearman's correlation of approximately 0.4 [29], well below what we found in the present study. Other studies found kappas between 0.47 [11] and 0.9 [30], intraclass correlation (ICC) of 0.62 [31] and Yule's Y of 0.8 [32], being comparable or just below our correlation coefficients. In the cases where our study shows better agreement than previous studies, it is difficult to state whether this is due to the use of blood rather than urine, due to differences in sample populations or simply to statistical chance.…”
Section: Discussioncontrasting
confidence: 52%
“…Ideally, the collateral has frequent contact with the participant, especially in drinking situations. Statistically significant positive correlations have been found between collateral estimates of participant self-reported substance use (Babor et al, 1987; O’Farrell and Maisto, 1987), although poor collateral and participant agreement has been found in those with comorbid mental disorders (Stasiewicz et al, 2008). As more research indicates that self-reported drinking is often accurate, the use of collaterals has been discouraged as a way to obtain accurate reports of participant alcohol use (Babor and Del Boca, 1992; Babor et al, 1987, 2000;Maisto et al, 1990).…”
mentioning
confidence: 99%
“…Psychometric validation of the BFSQ was based on its implementation in an outpatient study group of adults recently treated naturalistically for an acute manic, hypomanic/manic, or depressive episode; performance characteristics of the BFSQ within more treatment‐resistant, chronically ill, or inpatient populations were not evaluated. In addition, although the use and abuse of alcohol and other substances are known to strongly influence patient functioning, these issues were not addressed within the BFSQ, in part due to the phenomenologic complexity of comorbid substance abuse, as well as the potential for unreliable self‐reporting of alcohol or substance misuse in dual‐diagnosis patients (56). Finally, it is also possible that other factors exist that may be relevant to functional status and were not identified either by the advisory panel or through cognitive testing in the study population, although the observed high degree of construct validity with other outcome measures would suggest that the contribution of any such unidentified factors is likely small.…”
Section: Discussionmentioning
confidence: 99%